2018
DOI: 10.1111/cei.13207
|View full text |Cite
|
Sign up to set email alerts
|

The potential role for infections in the pathogenesis of autoimmune Addison’s disease

Abstract: Autoimmune Addison's disease (AAD), or primary adrenocortical insufficiency, is a classical organ-specific autoimmune disease with 160 years of history. AAD is remarkably homogeneous with one major dominant self-antigen, the cytochrome P450 21-hydroxylase enzyme, which is targeted by both autoantibodies and autoreactive T cells. Like most autoimmune diseases, AAD is thought to be caused by an unfortunate combination of genetic and environmental factors. While the number of genetic associations with AAD is incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 120 publications
(153 reference statements)
0
9
0
2
Order By: Relevance
“…Addison’s disease is a primary adrenocortical deficiency resulting from damage to the adrenal cortex ( 7 , 8 ), which does not become clinically apparent until 80 to 90% of both adrenal cortices are destroyed ( 9 ). Causes of Addison’s disease include infections, infiltration, and hemorrhage, and most commonly in Western countries, autoimmunity ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addison’s disease is a primary adrenocortical deficiency resulting from damage to the adrenal cortex ( 7 , 8 ), which does not become clinically apparent until 80 to 90% of both adrenal cortices are destroyed ( 9 ). Causes of Addison’s disease include infections, infiltration, and hemorrhage, and most commonly in Western countries, autoimmunity ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Like with AAI, the pathogenesis of many autoimmune conditions remain unclear but an interplay between genetic predisposition and environmental factors, such as viral and bacterial infection, are thought to play a major role ( 9 , 11 , 12 ). Certain viruses could partake in development of AAI either by infecting steroid hormone-producing cells of the adrenal cortex or by affecting the balance of the immune system ( 9 ). Autoimmunity can be induced by infectious agents via varying mechanisms, such as epitope spreading, standard activation, and autoinflammatory activation of innate immunity, to name a few ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, even though the genotype does not correlate with the phenotype, we could speculate that it may predict the etiology of the disease. In that case, patients with damaging variants in innate immune genes may share the same triggers, such as viral infections, initiating or perpetuating the immunological attack of adrenal tissue [70] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is also known that acute infectious diseases may induce bilateral adrenal bleeding or adrenal venous thrombosis, leading to acute adrenal insufficiency and mortality excess in fatal sepsis [207]. In addition, adrenal insufficiency may result from a direct or immune-mediated adrenal injury after different acute infectious diseases, mostly with viral etiology [208]. For instance, autoptic studies in SARS deceased patients had shown degeneration and necrosis of adrenal cortical cells, and SARS-CoV was identified in the adrenal glands, possibly confirming a direct cytopathic effect [209].…”
Section: Adrenal Glandmentioning
confidence: 99%